Onyx car / Muhamad Firdaus Muhamad Izhar - Muhamad Izhar, Muhamad Firdaus (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Onyx is a car designed with the concept of an autonomous hatchback and added with autonomous (self-driving) AI features. Onyx is also a new concept for the new hatchback design which has been added with a cargo compartment in the front bonnet to increase the cargo area. Onyx is also a design that adds elements from the Mazda 3 and is also a concept car